Saúde mental e cidadania : ações e desafios da política pública de saúde mental do município de Maringá - PR - Marini, Silvia (2012)
The construction of Brazilian's public policy on mental health is a result of the organization of the Psychiatric Reform Movement, criticizing the assistance offered, which is based on the principles of the traditional organicist psychiatry. This kind of assistance made the violation of the basic and essential rights of people with psychic suffering possible for a long time. Therefore, the new public policy compromises socially with ensuring users respect and citizenship. Considering the importance of implementing actions that ensure this compromise, this research sought to understand the normative elements that support the concept of modern citizenship and its relationship to the processes of struggle and conflict in favor of the statement and guarantee rights of people with psychological distress. And thus identify in what extent actions practiced by the policy on mental health in the town of Maringá-PR, represented by two assistance services (CAPS AD e CAPS II), has been contributing to the building and ensuring of users citizenship. In this regard, bibliographic and documental research on the subject was conducted as well as semi-structured interviews with samples of users of the already mentioned services, with the managers of the mains specialized assistance services and with the coordinator of the town's policy. It was concluded that quality psychiatric assistance based on welcome and bond is the main contribution of the services to ensure the users citizenship. It was also concluded that some challenges need to be overcome to ensure users full citizenship, the main ones being: increased professional qualification in order to avoid the reproduction of discrimination as well as authority and guardianship relationships in the services; the establishment of intersectoral actions with other public polices so that all rights can be accessed.